Study of Thermal Behavior of Phase Change Material Based Fatty Acid Encapsulated PLA for Gypsum Board Application - Aidy, Nurhanifa; Teuku Rihayat; Lindawati; Iqbal; Mahyuddin (LPPM Politeknik Aceh Selatan, 2025)
Phase Change Material is one form of renewable energy utilization that can be applied to the walls of a house to support the work of the AC to be more efficient. This material works by absorbing solar heat energy, storing it, then releasing it out so that the wall does not conduct heat into the room which will affect the workload of the AC. Lauric and stearic fatty acids are one of the superior PCM forming materials. In this study, PCM was made using a mixture of eutectic fatty acids modified with lactic acid. The method used is the direct mix method (direct mixing). PCM fatty acid materials (Laurate-Stearate) are combined into a binary mixture of eutectic fatty acids at a composition of 86%: 14% w/w. Furthermore, modifications are carried out with poly lactic acid (P) in three composition variations (L-S):P, namely (0.5: 1), (0.7: 1.0), (0.9: 1.0). Samples will be prepared in a laboratory scale model and their energy analysis will be carried out. Based on DSC testing, it was concluded that the highest latent heat was achieved by sample LSPb with a value of 101.53 J/g. The second place was taken by sample LSPc, followed by LSPa and the lowest latent heat was sample GLSP0. In line with this, the lowest melting point as an indication that PCM can withstand hot air temperatures is also found in sample LSPb . Among the four test samples, TGA data showed that sample LSPb was the sample that had the best thermal stability among the other samples with the furthest onset and endset values and the smallest % weight loss with values of 154.60 oC, 191.11 oC and 3.87% weight loss, respectively. The use of 0.7 times the amount of poly lactic acid to the eutectic mixture can absorb heat best. However, the excessive amount of poly lactic acid added actually causes a decrease in the absorption capacity and the ability to maintain heat in the PCM sample. The eutectic mixture of lauric and stearic fatty acids and the addition of poly lactic acid in the gypsum matrix successfully formed PCM which can be a candidate for room temperature control material in energy-efficient building wall applications.